The Mechanical Properties of Laminated Composites Reinforced With Discontinuous and Continuous Different Fibers - AL-Nesearawi, M. A. ` (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we investigate how do the laminated composites behave mechanically when subjected to external stresses, when reinforced with continuous fibers (mat) and discontinuous fibers (chopped) and to find the effect of the fiber type on the mechanical properties. Laminated composites consisting of wood- wood and Ph-F resin as suitable adhesive were reinforced with different fibers(jute, glass, and carbon).However, two  different methods of reinforcement namely, mat and chopped fibers were utilized. The mechanical properties such as (impact strength, compression strength, tensile strength, shear strength, bending strength, and elasticity modulus) of laminated composites were measured. Fibers reinforced laminated composite exhibited better mechanical properties than anreinforced composite. Furthermore, Carbon fibers reinforced laminated composite exhibited better mechanical properties than both jute and glass fibers reinforced composite. All used fibers of laminated composite showed that distribution as mat rather than as chopped, where the increase in the total strength of laminated composite was observed as mat.